Controversial issues of diagnosis and systematics obsessive disorders - V. I. Krylov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article discusses the phenomenological essence, the diagnostic and prognostic value of different options obsessive disorders. Discusses discriminatory signs phobias, obsessions and compulsion. Analyzes existing approaches to the systematics of obsessions.